ANTHROPOMORPHISM IN MEDIA LINGUISTICS: FUNCTIONS, MECHANISMS, AND IMPACT (Neo Scientific Peer Reviewed Journal, 2026)
This article examines anthropomorphism as a key communicative and cognitive strategy in media linguistics. Defined as the attribution of human characteristics to non-human entities, anthropomorphism plays a significant role in shaping audience perception, emotional engagement, and narrative interpretation across modern media formats. The study analyzes its application in advertising, animation, and video games using a qualitative methodology that combines content analysis, discourse analysis, and audience interviews.The findings demonstrate that anthropomorphism enhances emotional resonance, simplifies complex concepts, and strengthens audience identification with media content. At the same time, it may contribute to distorted perceptions of artificial intelligence and digital technologies. The study highlights the dual nature of anthropomorphism as both an effective communicative tool and a potential source of cognitive bias.